The two salinity peaks mode of marine salt supply to coastal underground brine during a single tidal cycle - Xiao, Xiaoteng; Zhang, Yufeng; Fu, Tengfei; Sun, Zengbing; Lei, Bingxiao; Li, Mingbo; Guo, Xiujun (Frontiers in Marine Science, 2024)
Seawater salt is constantly supplied from the marine environment to coastal underground brine deposits, meaning that brine has the potential for continuous extraction. There is currently a lack of information about the processes that drive the fluxes of seawater salt to underground brine deposits in tidal-driven brine mining areas. We chose the Yangkou salt field on the southern coast of Laizhou Bay, a brine mining area, as our study site. We monitored the spatial and temporal distribution of the underground brine reserve and the changes in water level and salinity in the mining area and adjacent tidal flats using electrical resistivity tomography and hydrogeological measurements. We monitored cross-sections along two survey lines and observed that the underground brine reserve receives a stable supply of seawater salt, and calculated that the rate of influx into the brine body in the mining area near the boundary of the precipitation funnel was 0.226−0.232 t/h. We calculated that a total salt flux of approximately 5.50 t enters the underground brine body every day through a 150 m long shoreline and a 1322.3 m2 window, which is sufficient to sustain the daily extraction of one brine well. During tidal cycles, there are two peaks in the salinity of the water supplied to the underground brine reserve, which means that the brine supply is from at least two high-salinity salt sources in different tidal stages. The first salinity peak occurs during the initial stage of the rising tide after seawater inundates the tidal flat. At this time, seawater, which is a solution and carries a large amount of evaporated salt, is transported into the brine layer through highly permeable areas or biological channels and replenishes the brine in the mining area. The second salinity peak occurs during the early stage of the falling tide. Influenced by hysteresis-driven tidal pumping, high-salinity brine from the lower intertidal zone is rapidly transported into the mining area, thereby increasing the salinity of the underground brine.